Epidermal to Mesenchymal Transition and Failure of EGFR-Targeted Therapy in Glioblastoma - Pala, Andrej (MDPI, 2012)
Glioblastoma multiforme (GBM), the most common primary brain tumor in adults, is almost never curable with the current standard treatment consisting of surgical resection, irradiation and temozolomide. The prognosis remains poor despite undisputable advances in the understanding of this tumor’s molecular biology and pathophysiology, which unfortunately has so far failed to translate into a meaningful clinical benefit. Dysregulation and a resulting prominent pathophysiological role of the epidermal growth factor receptor (EGFR) have been identified in several different malignant tumor entities, GBM among them. The EGFR is overexpressed in about 40% of GBM cases, and half of these coexpress a mutant, constitutively activated subtype, EGFRvIII. Unfortunately, recent trials studying with therapeutic approaches targeted against the EGFR and EGFRvIII have failed to meet expectations, with only a minority of patients responding despite evidence of good in vitro and rodent model activity. Having potentially high relevance within this context, epithelial to mesenchymal transition (EMT) is a phenomenon associated with early stages of carcinogenesis, cancer invasion and recurrence. During EMT, epithelial cells lose many of their epithelial characteristics, prominently E-cadherin expression, and acquire properties that are typical for mesenchymal cells such as the expression of vimentin. Epithelial to mesenchymal transition has been specifically demonstrated in GBM. In this review, we summarize the evidence that EMT may precipitate GBM resistance to EGFR-targeted therapy, and may thus be among the principal factors contributing to the clinical failure of targeted therapy against EGFR and EGFRvIII.